Instilling the Habit of Reading in the First Republic of Lithuania: Public State Libraries in Small Towns - Tarvydaitė, Dominyka (Lietuvos istorijos studijos, 2025)
The article investigates the process of setting up a network of public State libraries and their development in the smaller towns in the First Republic of Lithuania. By referring to analysis of the applicable legal regulation and archival sources, the development of the role of public libraries and their objectives is recreated by focusing on the effort to promote reading in provincial Lithuania, along with research of practical aspects of founding these libraries and running them in the smaller towns. By sourcing examples from small-town libraries, historiography knowledge is expanded on the development of cultural practices in minor settlements in interwar Lithuania.
Keywords: public library; reading; education; small town; Lithuania in 1918–1940